2020
DOI: 10.1088/1755-1315/451/1/012065
|View full text |Cite
|
Sign up to set email alerts
|

Water quality analysis of bribin underground river as the source of raw water for a government-owned water company (pdam) in the bribin management unit, Gunungkidul regency-Indonesia

Abstract: Bribin Underground River supplies raw water for a government-owned water company, PDAM, and has more potential than the other three of its sources, namely Baron, Seropan, and Ngobaran. In addition to sufficient quantity, raw water has to meet a set of water quality standards. This research was intended to describe the quality of raw water from the source to the service areas spatially. The water quality was measured directly in the field and then in the laboratory using the water samples collected by the purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…On the four service lines, the distribution pattern showed that the farther the distance to the raw water sources/intakes (Baron and Ngobaran Underground Rivers), the higher the pH value (Figure 4). This pattern is similar to the drinking water quality of PDAM Seropan [6] and PDAM Bribin [7].…”
Section: Degree Of Acidity (Ph)supporting
confidence: 77%
“…On the four service lines, the distribution pattern showed that the farther the distance to the raw water sources/intakes (Baron and Ngobaran Underground Rivers), the higher the pH value (Figure 4). This pattern is similar to the drinking water quality of PDAM Seropan [6] and PDAM Bribin [7].…”
Section: Degree Of Acidity (Ph)supporting
confidence: 77%